Penanganan Tindak Pidana Penipuan Online melalui Alat Bukti Digital di Kepolisian Surakarta: Perspektif Hukum Positif dan Hukum Islam - Diana Berlian Nurjanah; Masrukhin Masrukhin (IAIN Langsa, 2026)
This study aims to analyze the patterns of handling online fraud crimes through digital evidence at the Surakarta Police and to assess their conformity from the perspectives of Indonesia’s positive law and Islamic criminal law. This research employs field research complemented by library research, using a qualitative approach with a juridical-empirical and normative-comparative method. The findings indicate that the use of digital evidence in investigative practices has largely complied with the Indonesian Criminal Procedure Code and the Electronic Information and Transactions Law, although it remains constrained by technical verification issues and the maintenance of the chain of custody. From the perspective of Islamic criminal law, digital evidence may be positioned as qarinah that possesses evidentiary value insofar as it fulfills the principles of al-bayyinah. This study demonstrates the normative convergence between positive law and Islamic law in strengthening a substantively just model of criminal proof in the digital era.